207k views
5 votes
Imothy evaluated the expression using x = 3 and y = –4. xy-2 3x2y−4 1. (1 3 )x−1y2 2. (1 3 )3−1(−4)2 3. (1 3 )(1 31 )(−4)2 4. (1 3 )(1 3 )(−16) 5. −16 9 Analyze Timothy's steps. Is he correct? If not, why not? Yes, he is correct. No, he needed to add the exponents when he simplified the powers of the same base. No, he needed to multiply 3 and –1 instead of creating a positive exponent in a fraction. No, his value of (negative 4) squared should be positive because an even exponent indicates a positive value.

User ZunTzu
by
4.5k points

2 Answers

3 votes

Answer:

Explanation:

Imothy evaluated the expression using x = 3 and y = –4. xy-2 3x2y−4 1. (1 3 )x−1y-example-1
User Mseddon
by
4.9k points
3 votes

Answer:

No, his value of (negative 4) squared should be positive because an even exponent indicates a positive value.

Explanation:

The expression is not well written. The expression is written as;

(xy^-2)/(3x²y^-4)

According to indices;

a^m ÷ a^n = a^{m-n}

Applying this to solve the question

1/3(x^{1-2})/(y^-2÷y^-4)

= 1/3(x^{-1})(y^{-2+4})

= 1/3(1/x)y²

= 1/(3x) × y²

Substituting x = 3 and y = -4

= 1/3(1/3)×(-4)²

= 1/9(16)

= 16/9

Imothy solution is incorrect.

According to Imothy solution, his value of (negative 4) squared should be positive because an even exponent indicates a positive value.

User Darlington
by
5.6k points